Impact of digital finance on economic growth: evidence from selected ASEAN countries / Nur Syamimi Aqilah Mohamad Zainal - Mohamad Zainal, Nur Syamimi Aqilah (2021)
For a long term impact, the digital finance innovations could benefits to all users by expanding the access, low-cost services offered and increasing the convenience of the transactions. This research were to quantifying the potential economic and the benefits from the digital finance solutions to the individuals, businesses, financial institutions and also governments. This paper aimed to investigate the impact of digital finance on economic growth in the selected ASEAN countries. The study employed a sample from Indonesia, Thailand and Malaysia that using annually data taken from year 2010 until 2019. The study used secondary data that taken from World Bank Group. By using multiple regression analysis, the dependent variable was economic growth that measured by GDP per capita with the indicator of digital financial inclusion with the proxy of automated teller machine (ATMs), number of commercial bank branches and the individual using internet in the region observed. From the analysis, this study estimated that there is relationship between digital financial inclusion and economic growth in selected ASEAN countries.